PENGARUH UKURAN PERUSAHAAN, EFEK BID-ASK, LIKUIDITAS DAN HIPOTESIS REAKSI BERLEBIH TERHADAP FENOMENA PEMBALIKAN HARGA SAHAM PADA EMITEN INDEKS KOMPAS 100 DI BURSA EFEK INDONESIA PERIODE 2009-2013 - Pamela, Liely; -, Kamaliah; Safitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the size of the company, the Securities Bid-Ask, liquidity, excessive reaction hypothesis significantly influence the reversal phenomenon in the Issuer's Share Price Index 100 Compass in Indonesia Stock Exchange Period 2009-2013. This study uses the documentation, which the authors mmelakukan retrieval of data that has been provided by the Issuer Company Kompas 100 index in the Indonesia Stock Exchange Period 2009-2013. The statistical method used to test the hypothesis is multiple regression with the help of SPSS version 18.0. The results provide evidence that the Effect size of the company, the Securities Bid-Ask, Liquidity, reactions hypothesis Excess significantly influence the reversal phenomenon in the Issuer's Share Price Index 100 Compass in Indonesia Stock Exchange Period 2009-2013 through multiple correlation coefficient (R) of 0.562 or 56.2% and strong relationship.Keywords: company, likuidity, stock and issuers index.